Body Temperature and Activity Rhythms Under Different Photoperiods in High Arctic Svalbard ptarmigan (Lagopus muta hyperborea) - Appenroth, Daniel; Nord, Andreas; Hazlerigg, David; Wagner, Gabriela (Frontiers in Physiology, 2021)
Organisms use circadian rhythms to anticipate and exploit daily environmental oscillations. While circadian rhythms are of clear importance for inhabitants of tropic and temperate latitudes, its role for permanent residents of the polar regions is less well understood. The high Arctic Svalbard ptarmigan shows behavioral rhythmicity in presence of light-dark cycles but is arrhythmic during the polar day and polar night. This has been suggested to be an adaptation to the unique light environment of the Arctic. In this study, we examined regulatory aspects of the circadian control system in the Svalbard ptarmigan by recording core body temperature ( T b ) alongside locomotor activity in captive birds under different photoperiods. We show that T b and activity are rhythmic with a 24-h period under short (SP; L:D 6:18) and long photoperiod (LP; L:D 16:8). Under constant light and constant darkness, rhythmicity in T b attenuates and activity shows signs of ultradian rhythmicity. Birds under SP also showed a rise in T b preceding the light-on signal and any rise in activity, which proves that the light-on signal can be anticipated, most likely by a circadian system.